Acquired von Willebrand Syndrome in Patients With Ventricular Assist Device - Rauch, Antoine; Susen, Sophie; Zieger, Barbara (Frontiers in Medicine, 2019)
During the last decade the use of ventricular assist devices (VADs) for patients with severe heart failure has increased tremendously. However, flow disturbances, mainly high shear induced by the device is associated with bleeding complications. Shear stress-induced changes in VWF conformation are associated with a loss of high molecular weight multimers (HMW) of VWF and an increased risk of bleeding. This phenomenon and its cause will be elaborated and reviewed in the following.